Work-related well-being in early career: A role of self-compassion - Kristýna Krejčová; Igor Krejčí; Hana Chýlová; Pavla Rymešová; Pavel Michálek (Heliyon)
Several studies have demonstrated the positive effects of mindfulness and self-compassion on employee well-being, mental health, and resilience. The objective of this observational study was to explore the mutual relationships among the dimensions of self-compassion and particular characteristics of work-related well-being: work engagement, workaholism (excessive and compulsive work), and job boredom in a population of early career workers. In this quantitative cross-sectional study, 286 master's students with proper working experience were examined; results from 244 respondents were suitable for further data analysis. The Self-compassion Scale, Utrecht Work Engagement Scale, Dutch Work Addiction Scale, and Dutch Boredom Scale were administered. Spearman's rank correlation analysis found a positive relationship between work engagement and excessive work and a negative relationship between work engagement and job boredom. Furthermore, a positive correlation was identified between compulsive work and negative subscales of the Self-compassion Scale. Structural equation modeling indicated that workaholism was a mediator between the negative scales of self-compassion and work engagement with job boredom. In conclusion, the negative aspects of self-compassion (isolation, self-judgment, and over-identification) are related to the symptoms of workaholism in young workers. Self-compassion-based interventions could help prevent the negative effects of compulsive and excessive work. Possible age-related explanations for the positive relationship between work engagement and workaholism (i.e., excessive work) are discussed. Future longitudinal research could identify the dynamics of the connection between self-compassion and work-related well-being from a long-term perspective.